The condition a novel - Haigh, Jennifer 1968- (Harper Perennial, 2009)
Unaware of the long-standing grievances harbored by their divorced parents, three adult siblings embark on a tumultuous summer when the oldest, a successful Manhattan doctor, investigates his sister's chromosomal disorder against his mother's wishes